Decreased miR‐200a‐3p is a key regulator of renal carcinoma growth and migration by directly targeting CBL. Issue 12 (1st September 2018) - Ding, Meng; Sun, Xinlei; Zhong, Jinsha; Zhang, Cuiping; Tian, Yaping; Ge, Jingping; Zhang, Chen‐Yu; Zen, Ke; Wang, Jun‐Jun; Zhang, Chunni; Wang, Cheng
Abstract: Although emerging evidence has revealed that microRNAs (miRNAs) dysregulation contribute to carcinogenesis, the mechanism underlying their roles in renal cell carcinoma (RCC) is unclear. The purpose of the current study was to analyze the association of miR‐200a‐3p expression with RCC and to understand potential novel target genes, functions and mechanisms of miR‐200a‐3p in RCC. MiR‐200a‐3p expression levels were first measured by quantitative real‐time polymerase chain reaction and in situ hybridization in pairs of RCC tissue samples. Next, the potential miR‐200a‐3p target gene was analyzed using a combination of computer‐aided algorithms, luciferase reporter assays and Western blot analysis. Finally, the biological roles of miR‐200a‐3p in RCC tumorigenesis were investigated both in vitro by 5‐ethynyl‐20‐deoxyuridine, apoptosis assay and transwell assay, as well as in vivo using a xenograft mouse model. Our results demonstrated that miR‐200a‐3p was remarkably downregulated in RCC tissues compared with normal adjacent tissue, and CBL is a direct target of miR‐200a‐3p. An inverse correlation between miR‐200a‐3p and CBL was observed in RCC tissue samples. Mechanistic investigations revealed that ectopic expression of miR‐200a‐3p in RCC cell lines suppressed cell proliferation and migration and enforced cell apoptosis by directly inhibiting CBL in vitro and in vivo, whereas silencing miR‐200a‐3p resulted in the opposite effects. Additionally, overexpressing CBL abolished the effects induced by miR‐200a‐3p overexpression. Taken together, our results show that the miR‐200a‐3p/CBL regulation axis is a novel mechanism underlying RCC pathogenesis and may serve as a candidate biomarker and therapeutic target in RCC. Abstract : Although emerging evidence has revealed that microRNAs (miRNAs) dysregulation contribute to carcinogenesis, the mechanism underlying their roles in renal cell carcinoma (RCC) is unclear. In this study, we show that the miR‐200a‐3p/CBL regulation axis is a novel mechanism underlying RCC pathogenesis and may serve as a candidate biomarker and therapeutic target in RCC.